TAX REFORM AS THE NEED OF THE HOUR - Syniavska Л. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The purpose of the article is to study the ongoing reforming of the tax system of Ukraine. It is noted that the problems of the tax system remain the most serious among the obstacles to conducting business and filling the treasury. The reform of the tax and customs service continues, but it is still extremely difficult to predict its effectiveness. It is emphasized that taxes have become the most important method to accumulate financial resources by the state, which provides the lion’s share of budget revenues. It was noted that the decrease in their share during 2022–2023 is the result of established tax breaks and reliefs to support businesses and citizens during martial law. Among many reforms of the State Tax Service, the main focus is on the package of changes to the tax system of Ukraine, which was named «Tax Reform 10-10-10» and the adopted National Revenue Strategy for 2024–2030. The goal of this reform is emphasized, which is to reduce the tax burden for businesses and citizens, which, in turn, should positively affect economic growth. It is noted that the strategy is one of the conditions of the International Monetary Fund in the framework of cooperation with Ukraine during the four-year program, will be valid until the end of March 2027, provides for the allocation of 15.6 billion dollars to Ukraine, and contains both useful and controversial proposals for the economy. Special attention is paid to the proposed reform of the simplified taxation system (STS), which provides for the revision of the list of branches of activity admitted to the first group to exclude high-turnover businesses with a set rate from the actual income received; combining the second and third groups of the simplified taxation system into one group with a differentiated scale; introduction of a single tax rate for legal entities of the third group with a gradual increase to the level of the ordinary income tax rate (18 %). It was concluded that an increase in the tax burden and the introduction of additional duties for payers of the simplified system may lead to the termination or liquidation of part of the business since it will be suboptimal for them to work under the new rules, which will have negative consequences for the budget, employment, labor migration, and other aspects of the economy.